DENS INVAGINATUS TIPO III: REPORTE DE UN CASO (2011)
Dens invaginatus is a developmental disorder that is caused by an invagination of the inner epithelium of the enamel organ, inside dental papilla, during the early stages of morphodifferentiation of multifactorial etiology. A case of a 9 years-old female patient is presented, during the clinical examination it was observed fistula and the right central incisor with macrodontia, the patient referred no history of pain or trauma. Radiographically, it was observed an invagination that crosses the root forming two apical foramina, so that was diagnosed as type III dens invaginatus with pulp necrosis